On Gnoseological Roots of Religion - Černienė, Bronislava (Problemos, 1975)
In the article various interpretations of the Leninist idea of gnoseological roots of the origin of religion are considered, an attempt is made to explicate its real methodological contents. The analysis of the fragment “To the Question of Dialectics” leads to the thought that one must search for the gnoseological roots of the origin of religion not in the consciousness or in the peculiarities of human psychics but in cognition as the socio-historical process or, more concretely, in the specific peculiarities of the cognition process of the primitive society. Anthropomorphization of reality understood as cognition method, conditioned by the level of practical conquering of nature at the formation of humanity, led to the idea of the dependence of primitive people on anthropomorphic beings, to worshiping and the cult, i.e., to religion. The anthropomorphic character of the primitive cognition process is the real gnoseological prerequisite for the origin of religion in the primitive society.